2019
DOI: 10.3390/pharmaceutics11120684
|View full text |Cite
|
Sign up to set email alerts
|

Aptamers as Delivery Agents of siRNA and Chimeric Formulations for the Treatment of Cancer

Abstract: Both aptamers and siRNA technologies have now reached maturity, and both have been validated with a product in the market. However, although pegaptanib reached the market some time ago, there has been a slow process for new aptamers to follow. Today, some 40 aptamers are in the market, but many in combination with siRNAs, in the form of specific delivery agents. This combination offers the potential to explore the high affinity and specificity of aptamers, the silencing power of siRNA, and, at times, the cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…Many studies have demonstrated the efficacies of aptamer-siRNA chimeras as targeted delivery, anti-cancer, or anti-viral therapies. This includes studies against various cancers such as lung carcinoma, melanoma, breast, and lymphoma [58][59][60][61] as well as against HIV by targeting the cell surface markers such as CD4, C-C chemokine receptor type 5 (CCR5), and glycoprotein 120 (gp120) [34,[62][63][64]. Therefore, presenting the potential of this combination as a useful dual-functioning antiviral treatment against SARS-CoV-2.…”
Section: Aptamersmentioning
confidence: 99%
“…Many studies have demonstrated the efficacies of aptamer-siRNA chimeras as targeted delivery, anti-cancer, or anti-viral therapies. This includes studies against various cancers such as lung carcinoma, melanoma, breast, and lymphoma [58][59][60][61] as well as against HIV by targeting the cell surface markers such as CD4, C-C chemokine receptor type 5 (CCR5), and glycoprotein 120 (gp120) [34,[62][63][64]. Therefore, presenting the potential of this combination as a useful dual-functioning antiviral treatment against SARS-CoV-2.…”
Section: Aptamersmentioning
confidence: 99%
“…The small interfering RNAs (siRNAs), are a promising approach for gene therapy, however their intracellular administration remains difficult. To date, a great variety of delivery system for siRNAs has been investigated such as lipids, polymers, aptamers and cell penetrating peptides (CPPs) [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. In this regard, CPPs appear as a new class of transporters, which increase intracellular uptake of biologically active molecules including siRNAs [ 45 ] ( Figure 2 ).…”
Section: Benefit Of Cpps Used As Vehicles In Oligonucleotides Delimentioning
confidence: 99%
“…Several nanomaterials have been used for siRNA delivery like lipid nanoparticles, polymer nanoparticles, exosomes, aptamers, and inorganic nanoparticles. , Cationic polyelectrolytes and lipids are without any doubt the most efficient in complexing siRNAs through their positive charges via electrostatic interactions. However, positive charges induce toxicological endpoints over a certain concentration, limiting the therapeutic outcome.…”
Section: Introductionmentioning
confidence: 99%